Comparison of short pulse generation schemes for a soft x-ray free electron laser - Martin, I; Bartolini, R (2011)
In this paper we study the performance of two complementary short pulse generation schemes as applied to a soft x-ray free electron laser. The first scheme, recently proposed by Saldin et al., makes use of a laser pulse consisting of only a few optical cycles to give an energy chirp to a short section of an electron bunch and tapers the main radiator undulator in order to compensate the chirped region. The second scheme investigated takes a low-charge, high brightness electron bunch and compresses it to ∼1fs in order to operate in the so-called "single-spike" regime. We perform start-to-end simulations of both these schemes, assess the sensitivity of each scheme to realistic jitter sources, and provide a direct comparison of the respective strengths and drawbacks. © 2011 American Physical Society.